Harnessing Group-Level Influence to Boost Energy-Savings Behavior in the Office Building - Do, Tuan Anh; Nguyen, Tung Thanh; Duong, Kien Trung (International Journal of Energy Economics and Policy, 2023)
Using energy saving and effectively is one of the measures to ensure energy security in urban areas. Research on energy-saving behavior in buildings is one of the approaches to improving energy usage efficiency. This study explores the mechanisms that influence the energy-saving intention (EI) and energy-saving behavior (EB) of individuals in shared spaces, including the Self-transcendence group Values (SV), Descriptive Norm (DN), Group Interaction (GI), and Energy management board (MB). The research model proposed ten hypotheses based on the theory of Dynamic group, and data was collected through a direct survey questionnaire from 295 samples and analyzed using Structural Equation Modeling (SEM). The results show that descriptive norms, i.e., the actions of other members in the group, have the highest impact on the energy-saving behavior of individuals in shared spaces. Group interaction helps to increase the likelihood of acting and, therefore, reinforces the intention to save energy. The Energy management board indirectly influences the energy-saving behavior of individuals through their intention to save energy. These findings can contribute to the development of energy-saving strategies in shared spaces, focusing on descriptive norms, rather than the current approach based on instructions. Furthermore, the experimental research results can provide guidance for policymakers in developing strategies to change energy-saving behavior in buildings in urban areas in Vietnam.